(untitled) (Journal of Bio-Science, 2009)
The efficacy of seven different plant extracts viz. Acorus calamus rhizome, leaves of Datura fastuosa, Datura stramonium and seeds of D. stramonium, Corchorus capsularis, Aphanamixis polystachea and Jatropha curcas on Tribolium confusum adult was studied. Dose mortality experiments were conducted with three solvent (petroleum ether, acetone and methanol) extracts separately but J. curcas seed was tested with petroleum ether extract only. Among three solvents, petroleum ether extract exhibited piquant toxic effect against the beetle at all the intervals although D. fastuosa leaf produces no mortality at 24 hours of treatment. Acetone extract of A. calamus rhizome, D. fastuosa leaf, D. stramonium seed and C. capsularis seed produced mortality at all the intervals but D. stramonium leaf and A. polystachea seed did not show any toxic effect. Methanol extract of C. capsularis seed showed toxicity at all the duration. Key words: Toxic effect, plant extracts, Tribolium confusum. Â doi: 10.3329/jbs.v15i0.2153 J. bio-sci. 15: 133-138, 2007